Qianlie Xiaozheng Decoction Induces Autophagy in Human Prostate Cancer Cells via Inhibition of the Akt/mTOR Pathway - Xu, Yuehua; Cai, Xueting; Zong, Bin; Feng, Rui; Ji, Yali; Chen, Gang; Li, Zhongxing (Frontiers in Pharmacology, 2018)
Qianlie Xiaozheng decoction (QLXZD), a traditional Chinese medicinal formula, has been used clinically to treat advanced prostate cancer (PCa) for more than 10 years. However, experimental evidence supporting its efficacy is lacking. Here, we investigated the anticancer properties and molecular mechanism of QLXZD in vitro in a human PCa cell line (PC3) and in vivo using PC3 xenografts in nude mice. We confirmed the antineoplastic activity of QLXZD by analyzing cell viability and tumor volume growth, which decreased significantly compared to that of the controls. Autophagy following QLXZD treatment was detected morphologically using transmission electron microscopy and was confirmed by measuring the expression of autophagy markers (LC3-II and p62) using fluorescence analysis, flow cytometry, and western blotting. Increasing autophagic ﬂux induced by QLXZD was monitored via pmCherry-GFP-LC3 fluorescence analysis. QLXZD-induced autophagic cell death was alleviated by the autophagy inhibitors, 3-methyl adenine and hydroxychloroquine. We evaluated the total expression and phosphorylation levels of proteins involved in the Akt/mTOR pathway regulating autophagy. Phosphorylation of Akt, mTOR, and p70S6K, but not total protein levels, decreased following treatment. This is the first study to demonstrate the autophagy-related mechanistic pathways utilized during QLXZD-mediated antitumor activity both in vitro and in vivo. These findings support the clinical use of QLXZD for PCa treatment.